Voice and viewpoint in journalistic narratives. (July 2020) - Głaz, Adam; Trofymczuk, Anastazja
Abstract: It is argued in this study that research on viewpoint in language use provides better results if the category of voice is recognized as a semi-autonomous construct in relation to viewpoint. Voice is understood here as the "who" in the act of speaking but not identified with the actual speaker. Rather, it is a category of discourse that can be "abstracted", to some extent, from the broader viewpoint phenomenon. A corpus of journalistic narratives from British quality press and American national press has been analyzed, on the basis of which a theoretical and terminological framework is being proposed. The basic distinction is that between single and multiple voices. As discourse develops, single voices shift from one to another in an abrupt or gradual manner. Multiple voices, in turn, can be "heard" as polyphonic, blended, or fused, depending on the degree of their integration (intertwining), with fused voices resulting in a single collective voice. However, voice is not a fully autonomous category, as it is shown to be closely interlinked with several types of viewpoint. Because this study is based on data from a specific genre of English-language journalism, it is also an invitation to test and expand the framework proposed in analyses of other genres in English and in other languages. Highlights: Voice is semi-autonomous in relation to viewpoint. Journalistic narratives from British quality press and American national press. Single voices undergo abrupt or gradual voice shift. Multiple voices are polyphonic, blended or fused – the latter yield collective voice. Voice is closely interlinked with several types of viewpoint.